pH and ferning score of cervical mucus related to gestation and calf gender of Holstein Friesian crossbreed cows - Ferdiansyah, Muhammad Billy; Hamid, Iwan Sahrial; Hermadi, Herry Agus; Samik, Abdul; Hernawati, Tatik (Ovozoa: Journal of Animal Reproduction, 2022)
This study aimed to compare the ferning score based on the pH of the cervical mucus and its relation with gestation and the calf gender of cows. Ten Holstein Friesian crossbreed cows which were detected in estrus and about to be artificially inseminated, were used for this study. Sample of cervical mucus was collected using Metricheck for pH and ferning observations. Pregnancy diagnosis was conducted two months after insemination, and the gender of the calves was recorded at parturition. This study indicated that cervical mucus pH did not affect the ferning characteristics, ferning score, and pregnancy of cows. However, higher ferning scores tended to result in the pregnancy of cows. Also, alkaline pH tended to result in male calves and vice versa. Further study is needed with a more significant number of samples related to the application of ferning display as an indicator of estrus to obtain a higher pregnancy rate.